Is transanal irrigation the best treatment possibility for low anterior resection syndrome? A multicenter, randomized clinical trial: study protocol - Klimovskij, Michail; Civilka, Ignas; Aleinikov, Andrej; Aukstikalnis, Tomas; Christensen, Peter; Dulskas, Audrius (Frontiers in Surgery, 2024)
Background Up to 50% of patients who undergo rectal resection suffer from various and partly severe functional problems, despite the preservation of the anal sphincter. These complaints are defined as low anterior resection syndrome (LARS). So far, there are no randomized clinical trials regarding the most effective treatment for LARS. Our aim is to evaluate whether transanal irrigation improves bowel function and quality of life in patients following low anterior resection compared to best supportive care. Methods Patients who have undergone low anterior resection will be approached for this study. On patient's visit, complaints regarding the defecation as well as any deterioration in their overall quality of life will be assessed using questionnaires such as the Low Anterior Resection Syndromes score, Wexner score, European Organization for Research and Treatment of Cancer (EORTC) Quality of Life (QOL) CR-29, and Measure Yourself Medical Outcome Profile tool. Few additional target questions will be also asked, such as “Would you recommend the treatment to anybody; did you expect the improvement following the treatment; etc.” Questionnaires and scales will be filled on follow-up visits every 3 months for 1 year. Discussion This multicenter, randomized controlled trial will lead to a better understanding of LARS treatment. Moreover, it will be a hypothesis-generating study and will inform areas needing future prospective studies. Clinical Trial Registration ClinicalTrials.gov, identifier (NCT05920681).